SYSTEM FOR ACCOUNT AND STATISTICAL ANALYSIS OF PATIENTS WITH THE DIAGNOSIS OF EPILEPSY - Stetsyuk, V. Z.; Babintseva, L. Yu.; Ivanova, T. P.; Fedyshka, H. M.; Chyzh, Yu. M.; Muha, I. P. (Medical Informatics and Engineering, 2020)
Background. Epilepsy is a central nervous system (neurological) disorder in which brain activity becomes abnormal, causing seizures or periods of unusual behavior, sensations, and sometimes loss of awareness. Anyone can develop epilepsy. Epilepsy affects both males and females of all races, ethnic backgrounds and ages. Seizure symptoms can vary widely. Having a single seizure doesn't mean you have epilepsy. At least two unprovoked seizures are generally required for an epilepsy diagnosis. Treatment with medications or sometimes surgery can control seizures for the majority of people with epilepsy. Some people require lifelong treatment to control seizures, but for others, the seizures eventually go away. Some children with epilepsy may outgrow the condition with age. After studying and analyzing the problems of this field, we decided to develop a computer program for optimizing the process of accounting and automation of statistical analysis of patients diagnosed with epilepsy of the department of neurology. The purpose of this work is to develop a computer desktop application «System for account and statistical analysis of patients with the diagnosis of epilepsy». Materials and methods. The research material is the work of a neurologist, who is engaged in the diagnosis and further treatment of diseases related to the activity of the nervous system, namely diseases of epilepsy. Results. The result of the research of the work of the department of neurology staff of the children's hospital and the analysis of the necessary accounting documentation is a system that optimizes the work of the department's staff. Applied computer program is installed on any number of computers in the department, integrated into the local network. The database is installed on the server or one of the computers on the local network. The program incarnates the following functions: accounting of the patients; filtering patients by selected criteria; saving basic information about each patient; dynamic management of the presence of the necessary diagnosis according to the classification of the International Antiepileptic League (ILAE Classification of the epilepsies); formation of reporting for specified periods with the possibility of viewing and printing information according to certain indicators; visualization of the results of statistical analysis using diagrams of different types. Conclusions. The main result of the work is the program, which ensures optimization of the work of the department of neurology staff.